2005
DOI: 10.1021/ja055658x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Ultrafast Molecular Elimination Reactions

Abstract: Ultrafast molecular elimination reactions are studied using the velocity map ion imaging technique in combination with femtosecond pump-probe laser excitation. A pump laser is used to initiate the dissociative reaction, and after a predetermined time delay a probe laser "interrogates" the molecular system. Ionic fragments are detected with a two-dimensional velocity map imaging detector providing detailed information about the energetic and vectorial properties of mass selected photofragments. In this paper we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…More recently, velocity map imaging 17,18 used in combination with pump-probe femtosecond laser pulses has demonstrated to be a powerful technique to study the real time dynamics of complex systems. 3,8,[19][20][21] Femtosecond imaging experiments include photoelectron 3,22 and photoionphotoelectron coincidence detection. 3,6,7,22 Here we have studied the femtosecond photodissociation dynamics of CH 3 I from the A band both experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, velocity map imaging 17,18 used in combination with pump-probe femtosecond laser pulses has demonstrated to be a powerful technique to study the real time dynamics of complex systems. 3,8,[19][20][21] Femtosecond imaging experiments include photoelectron 3,22 and photoionphotoelectron coincidence detection. 3,6,7,22 Here we have studied the femtosecond photodissociation dynamics of CH 3 I from the A band both experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…In 2000 we followed the German design notes of Gerlich in the construction of our first piezovalve that we operated at 1 kHz repetition rate in femtosecond ion imaging experiments. [14][15][16][17] Recent demands in our group 18,19 to run experiments at 5 kHz and the need to make translationally ͑and rotationally͒ cold pulsed molecular beams inspired us to reconsider the design of the cantilever piezovalve.…”
Section: Introductionmentioning
confidence: 99%
“…50 ee 315 Ultrafast molecular elimination of iodine from IF 2 C-CF 2 I has been studied using the velocity map ion imaging technique in combination with femtosecond pump-probe laser excitation. 51 By varying the femtosecond delay between pump and probe pulse, it has been found that elimination of molecular iodine is a concerted process, although the two carbon-iodine bonds are not broken synchronously.…”
Section: Other Reactionsmentioning
confidence: 99%